New Zealand : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2010)
This Selected Issues paper focuses on the issues of fiscal policy, rebalancing, and growth in New Zealand. The paper discusses that a key policy challenge for New Zealand is to rebalance the economy and reduce external vulnerabilities. It provides model-based estimates of the potential contribution that fiscal consolidation can make to external rebalancing and economic growth in New Zealand. The paper briefly describes the Global Integrated Monetary and Fiscal (GIMF) model, and provides some background on macroeconomic vulnerabilities and challenges in New Zealand.